Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1975
DOI: 10.1002/1097-0142(197502)35:2<347::aid-cncr2820350208>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Sequential therapy for induction and maintenance of remission in acute myeloblastic leukemia

Abstract: A total of 114 previously untreated patients with myeloblastic leukemia was included in a sequential therapy protocol. Daunorubicin, vincristine, and prednisone were employed for the first 3 weeks, followed by two or more 5‐day courses of cytosine arabinoside and 6‐mercaptopurine; there was a 5‐day rest between courses. Maintenance therapy was as follows: the continuing 6‐mercaptopurine and methotrexate treatment was interrupted every 30 days for sequential reinforcement courses consisting of one dose of dauno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

1976
1976
1980
1980

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
2
5
0
1
Order By: Relevance
“…Eppinger-Helft et al The observation that survival duration is longer in patients responding to chemotherapy is universal. For patients who attained at least one complete remission, the median survival in the AML-68 (12 months) and the AML-70 (16 months) studies is of the same order as the 10-19 months reported by others (20,21,24,28,33,38,39,42). Some reports suggest that the addition of immunotherapy may produce longer survivals (28,41).…”
Section: Survival Durationsupporting
confidence: 73%
See 3 more Smart Citations
“…Eppinger-Helft et al The observation that survival duration is longer in patients responding to chemotherapy is universal. For patients who attained at least one complete remission, the median survival in the AML-68 (12 months) and the AML-70 (16 months) studies is of the same order as the 10-19 months reported by others (20,21,24,28,33,38,39,42). Some reports suggest that the addition of immunotherapy may produce longer survivals (28,41).…”
Section: Survival Durationsupporting
confidence: 73%
“…Complete remission was induced in 57 of 86 previously untreated patients (66%) who entered studies in 1968-1973 with no significant differences between the 3 regimens (Table V). This frequency, although better than the 34% (21) to 38% (26) in series spanning many years, is of the same order as the 50-65% attained in the more successful studies of adults (20,26,(28)(29)(30)(31)(32) and the 42-57% in children reported by the Argentine Study Group (33,43). In fact, if one excludes the early deaths in this series the frequency of remission changes little (68%), while in adults the percentage improves by about 20% (26,28).…”
Section: Remission Inductionsupporting
confidence: 52%
See 2 more Smart Citations
“…The analysis of duration of remission was done on I August 1975. All these patients were treated systemically according to protocols recently published (Pavlovsky et al, 1973a;Sackniann Muriel ct al, 1974;Eppinger-Helft et al, 1975). Previous therapy for meningeal leukaemia or preventive CNS irradiation did not disqualify patients from this study.…”
Section: F Sackmann Muriel Et A1mentioning
confidence: 99%